PENINGKATAN KETERAMPILAN BERBICARA MELALUI METODE SOSIODRAMA PADA SISWA KELAS V SDN 1 PEMBINA AMPIBABO - Maryam, Maryam (BAHASANTODEA, 2016)
Speaking skill of the fifth grade students of SDN 1 Pembina Ampibabo can be improved with sociodrama method. It is stated from the research to the problem. The problems are : (1) how is the application of sociodramaÂ  method in improving speaking skill of the fifth grade students of SDN 1 Pembina Ampibabo ? And (2) how is the result of improvement speaking skill with using sociodrama method of the fifth grade students of SDN 1 Pembina Ampibabo ? therefore, kind of this research applicated by the researcher is classroom action research by colaborative which developed by Kemmis and Taggart with spiral model. While the subject of this reasearch is all of the student of fifth grade students at SDN 1 pembina Ampibabo which amount of the students is 34 tudents ( 20 boys student and 14 girls student) the researcher using the data accumulation method, they are test, observation and documentation. the data analisys tehnique is quantitative descriptive statistic, that is looking for the average score. The result of this research show that (1) the application of sociodrama method through five steps, the first step is the students prepared to pray and self preparation, conclude consentrate at the objective of learning. Second, the way of readig text explained by the teacher in order to the actor of the person characters can be done with accuracy way. Third, the students have a discussion with each other and teacher to understanding and going deep the role before they are exercise. Fourth, the students are motivated by the teacher to doing sociodrama which actioned with convey an opinion about the person i the story. Fifth, the students are motivated to hard study to speak in front of public which actioned with closing of learning through pray activity. After done that process, (2) students speaking skill have an improvement. The students speaking skill percentage have an improvement at each of meeting in cycle I and II. Speaking skill improvement at the cycle I is 7,38 from the first condition is 60,35 have improvement tobe 67,73. At the cycle II have improvement. It is 16,17, from the first condition is 60,35 have improvement tobe 76,52. In the last, can be concluded that the sociodrama method need to implemented to improving speaking skill through sociodrama method at the fifth grade students of SDN 1 Pembina Ampibabo.